Characterization of Melon, (Cucumis melo L.) Silage with Different Biomass Mixtures and Dry Matter Contents - Romilda Rodrigues do Nascimento; Ricardo Loiola Edvan; Keuven dos Santos Nascimento; Dhiéssica Morgana Alves Barros; Lucas de Souza Barros; Luan Felipe Reis Camboim; Tairon Pannunzio Dias e Silva; Rafael de Souza Miranda; Marcos Jácome de Araújo; Anisio Ferreira Lima Neto; Leilson Rocha Bezerra; Francisco Naysson de Sousa Santos; et al. (Agriculture, 2023)
The objective of this study was to obtain different dry matter contents and proportions of melon plant biomass for silage making. A completely randomized design with factorial arrangement (3 × 2) and four replications was adopted. The first factor consisted of three melon biomass mixtures based on as-fed composition of plant (branches + leaves) and harvested melon (fruits)—100% plant (0% fruit), 90% plant + 10% fruit, and 100% fruit. The second factor corresponded to the ensiled material, which was either fresh or dehydrated in the field after harvest (40% dry matter). Silages produced from dehydrated biomass after fruit harvest, containing 0% and 10% fruit, showed the highest dry matter contents: 297 g/kg and 293 g/kg, respectively. Silages produced from fresh biomass containing 0% and 10% fruit showed high concentrations of acetic acid, reaching 14.9 g/kg and 14.1 g/kg, respectively. Silages produced from dehydrated biomass containing 10% and 100% fruit showed better results in terms of the indicators associated with high-quality silage. Dehydration improves the fermentative profile and overall quality of melon silage.